Хипертензија и дијабетес мелитус - Г. Петровски; Ч. Димитровски; С. Садикарио; М. Богоев; Т. Миленковиќ (My University, 2004)
To evaluate hypertension in patients with Diabetes Mellitus (DM) and its correlation with age, duration of DM, Body Mass Index (BMI) and HbA1C).
Hypertension and diabetes mellitus